COMPARATIVE STUDY OF SONDONG FISHING EQUIPMENT IN VILLAGES PURNAMA WEST DUMAI DISTRICT OF DUMAI CITY WITH PERIGI RAJA VILLAGES KUALA INDRAGIRI DISTRICT OF INDRAGIRI HILIR REGENCY PROVINCE OF RIAU - Rindu, Mutiara; Sofyan, Irwandy; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research carried on 23 March – 06 April 2015, in the villages Purnama west Dumai District of Dumai city and then Indragiri Hilir Regency. With in comparative the contruction of fishing gear sondong city of Dumai for the fisherman in the Perigi Raja village. The research implemen using survey study and literature review. The results of this study indicate that Sondong on fishing gear, there are some similarities in sondong foot, footprint, and ropes fishing gear of sondong. The differentiation component of both of areas lies in the size of the mesh size net weight, while both have one bag. Based sondong fishing gear research, for foot sondong the best made by putut wood, in addition to strong material, and this wood is more economical. The greatest sondong it was in the Perigi Raja village , it because of the size of the net body bag there are 4 sections and each size of the mesh size of its already very good, because it does not take away all the small fish and other aquatic animals. Buoys and weights it according to the needs of each region because each region has a different sea state. Ropes of good materials from polyethylene because it is more environmentally friendly. The best catches are in rural areas Perigi Raja village because the sondong does not lift all small fish.Keyword : fishing gear of sondong,comparison, Dumai city,Indragiri Hilir Regency